The relationship between environmental awareness and university students' green entrepreneurial intention in Malaysia - Lee, Yingyan; Ling, Hsih Xin; Ng, Zhi Inn Gloria (2023)
The purpose of this research is to examine the relationship between environmental awareness and TPB theory which consists of attitude, behavioral control, and subjective norms, toward the green entrepreneurial intention among universities’ students in Malaysia. This study was conducted around 384 university students from two types of institutions which involved public institutions and private higher education institutions in Malaysia. In this study, 384 copies of survey questionnaires were handed out to those universities and IBM Statistical Package for the Social Sciences tool (SPSS) was used to analyses and interpret the relevant data. The data was analyzed by using descriptive analysis, reliability test, and Multiple Linear Regression. This research has tested that all IV (environmental awareness, perceived attitudes, perceived behavioural control, perceived subjective norms) have significant influence on green entrepreneurial intention. Nonetheless, there were some limitations and recommendation will be further discussed in this study as well.